Influencing immunity: role of extracellular vesicles in tumor immune checkpoint dynamics - Ziyang Ye; Genpeng Li; Jianyong Lei (Experimental and Molecular Medicine)
Abstract Immune checkpoint proteins (ICPs) serve as critical regulators of the immune system, ensuring protection against damage due to overly activated immune responses. However, within the tumor environment, excessive ICP activation weakens antitumor immunity. Despite the development of numerous immune checkpoint blockade (ICB) drugs in recent years, their broad application has been inhibited by uncertainties about their clinical efficacy. A thorough understanding of ICP regulation in the tumor microenvironment is essential for advancing the development of more effective and safer ICB therapies. Extracellular vesicles (EVs), which are pivotal mediators of cell–cell communication, have been extensively studied and found to play key roles in the functionality of ICPs. Nonetheless, a comprehensive review summarizing the current knowledge about the crosstalk between EVs and ICPs in the tumor environment is lacking. In this review, we summarize the interactions between EVs and several widely studied ICPs as well as their potential clinical implications, providing a theoretical basis for further investigation of EV-related ICB therapeutic approaches.